INTERACTIVE GLOBAL NETWORK FOR WEATHER DATA OBTAINING, EXCHANGE AND DISSEMINATION - Авер’янова, Ю.А. (Proceedings of National Aviation University (archive), 2012)
The possibility to enhance the weather information provision of relevant customers is considered. It is based on the use of the complex global system for weather information obtaining, exchange and dissemination. The structural diagram of the system is proposed. The structural diagram is completed with addition connections that allow to pay strong attention on the most dangerous meteorological phenomena at the critical moment of flight. The proposed approach gives possibility to aircraft crew to select and use specified operative information and increase the probability for proper decision taking. The aircraft are used as the dynamic elements for data obtaining and exchange in the frame of the global system for weather information obtaining, exchange and dissemination.